Feasibility of time-lapse seismic methodology for monitoring the injection of small quantities of CO2 into a saline formation, CO2CRC Otway Project - Pevzner, Roman; Urosevic, Milovan; Caspari, Eva; Galvin, R.; Madadi, M.; Dance, T.; Shulakova, V.; Gurevich, Boris; Tcheverda, V.; Cinar, Y. (Elsevier, 2013)
A key objective of Stage 2 of the CO2CRC Otway Project is to explore the ability of geophysical methods to detect and monitor injection of greenhouse gas into a saline formation. For this purpose, injection of some 10,000 30,000 tonnes of CO2-rich mixture into the Paaratte formation, a saline aquifer located at a depth of about 1,400 m, is planned. Before such an injection experiment is undertaken, we assess the feasibility of geophysical monitoring using computer modelling. To examine the detectability of the plume we need to estimate the time-lapse signal and time- lapse noise. The time lapse signal is modelled using flow simulations, fluid substitution and seismic forward modelling. In order to assess the applicability of time-lapse seismic to monitor the injection, the predicted signal is compared to the time-lapse noise level from the recent 4D seismic survey acquired at the Otway site in 2009-2010. The methodology is applied to two alternative reservoir intervals located at a depth of 1392-1399 m and 1445-1465 m below the sea level, respectively. These intervals are considered to be the two possible options for the injection. The results show that injection into the lower interval will produce a plume of a larger thickness and smaller lateral extent, and a seismic response that is more likely to be detectable. The developed feasibility assessment workflow, and the results of its application to the Otway site, can be used to assess the ability of seismic methods to detect and monitor greenhouse gas leakage in other CCS projects.